TARI SEBLANG BANYUWANGI SEBAGAI RITUAL MISTIS WUJUD SYUKUR - Aulya Nur Syahfitri, Qhaida (TANDA, 2023)
Banyuwangi, located in the province of East Java, is known not only for its natural beauty, but also as a home to the Osing tribe who have a rich and mystical culture. One of the most famous traditions is the Seblang Dance ritual, which is carried out by the Osing people in two villages in Glagah District, Banyuwangi Regency. This ritual aims to maintain the cleanliness of the village and as a form of warding off disaster, so that the village remains peaceful and protected from disaster. The uniqueness of the Seblang Dance lies in the condition of the dancers who are often in a trance or possessed by spirits, which is considered part of the process of summoning ancestral spirits to provide blessings and protection for the village. In this ritual, in addition to dancing, various series of activities are also carried out such as pilgrimage to ancestral graves, slametan, ider bumi, and a parade around the village. Every step in this ritual has a deep spiritual meaning. The Seblang Dance is also regulated by special provisions, starting from the selection of dancers who must meet certain age requirements, the use of typical accessories, to the time of implementation which is usually carried out in the month of Hajj or a week after Eid al-Adha. All of these processions not only show the community's gratitude to God and ancestors, but also reflect their efforts to maintain harmony between the spiritual and worldly worlds.